Behavioral outcome measures used for human neural stem cell transplantation in rat stroke models - Matthew B. Jensen; Dong Y. Han; Abdullah Al Sawaf; Rajeev Krishnaney-Davison (MDPI AG, 2011)
Stroke is a leading cause of death and disability, leading to the development of various stroke models to test new treatments, most commonly in the rat. Human stroke trials focus on disability, related primarily to neurological deficits. To better model the clinical application of these treatments, many behavioral tests have been developed using the rat stroke model. We performed a systematic review of all the behavioral outcome measures used in published studies of human neural stem cell transplantation in rat stroke models. The reviewed tests include motor, sensory, cognitive, activity, and combination tests. For each test, we give a brief description, trace the origin of the test, and discuss test performance in the reviewed studies. We conclude that while many behavioral tests are available for this purpose, there does not appear to be consensus on an optimal testing strategy.